THE IMPACT OF ECONOMIC STRUCTURE CHANGE ON THE LOCAL OWN SOURCE REVENUE AND ITS EFFECT TOWARDS THE REGIONAL INCOME IMPROVEMENT - Iskandar Ali Alam (International Conference On Law, Business and Governance (ICon-LBG), 2016)
Regional autonomy as the form of regional financial reform was planned to increase the regional finance, however the contribution of the central government to finance the Regional Revenue and Expenditure Budget through sharing of revenue, General Allocation Fund and Special Allocation Fund is still more dominant than the local own source revenue itself. In fact, the contribution of the local own source revenue to the regional revenue is still relatively low. This reflects that the sources of the local own source revenue are not yet optimally managed, especially from the economic structure change, potential tax and retribution which may affect the low revenue ratio. The research sample is Lampung Province, one of the poor provinces in Indonesia. The research applies the explanatory research method which is aimed at elaborating the causal relationship among variables and testing the hypothesis. The research findings show that the local finance improvement relies on local own source revenue of the present and previous years. On the other hand, the increase of local own source revenue relies on the contribution of economic structure change of regional financial improvement.